Topological mixing of Weyl chamber flows - Dang, Nguyen-Thi; Glorieux, Olivier (Ergodic theory and dynamical systems, 2021)
In this paper we study topological properties of the right action by translation of the Weyl chamber flow on the space of Weyl chambers. We obtain a necessary and sufficient condition for topological mixing.
Published online: 17 February 2020
Gesehen am 21.05.2021